Find the average rate of change for f(x)=2x^2-3x+5 from x=-1 to x=3

Printable View

- Mar 26th 2006, 01:31 PMbatman123Aroc - 2
Find the average rate of change for f(x)=2x^2-3x+5 from x=-1 to x=3

- Mar 26th 2006, 07:56 PMearbothQuote:

Originally Posted by**batman123**

The average rate of change is defined as: $\displaystyle \frac{\Delta f(x)}{\Delta x}$.

($\displaystyle \Delta$ means difference)

Now plug in the values you know and you'll get:

$\displaystyle \frac{f(3)-f(-1)}{3-(-1)}=\frac{14-10}{4}=1$.

Greetings

EB